Analisis Standar Perhitungan Zakat Profesi pada Baitul Mal Aceh - As'adi, As'adi (Jurnal Ilmiah Guru Madrasah, 2025)
Zakat is an essential instrument in Islam that serves to promote social equity and poverty alleviation. In the modern context, professional zakat (zakat al-mihnah) has emerged as a response to various types of income not explicitly mentioned in classical fiqh. In Aceh, professional zakat is managed by Baitul Mal Aceh, the official institution responsible for administering zakat, infaq, and sadaqah. This study aims to analyze the calculation standards of professional zakat applied by Baitul Mal Aceh, the legal and religious foundations used, and their conformity with Islamic principles and prevailing regulations. The research employs a qualitative descriptive-analytical method through document and literature review. The findings indicate that the calculation standards of professional zakat at Baitul Mal Aceh are formulated based on Islamic legal principles, scholars' fatwas, and national and regional regulations, particularly Law No. 11 of 2006 on the Government of Aceh and Aceh Qanun No. 10 of 2018 on Baitul Mal. The determination of nisab, zakat rate, and calculation mechanism is analogized to gold and silver zakat at 2.5% of income reaching the nisab equivalent to 94 grams of pure gold. The Sharia Advisory Council of Baitul Mal plays a crucial role in providing fatwas and ensuring Sharia compliance in zakat management policies. Thus, the professional zakat calculation standards implemented by Baitul Mal Aceh are consistent with Sharia principles and national regulations, reflecting efforts toward professionalism and transparency in zakat administration in Aceh. Abstrak Zakat merupakan instrumen penting dalam Islam yang berfungsi untuk pemerataan kesejahteraan sosial dan pengentasan kemiskinan. Dalam konteks modern, zakat profesi berkembang sebagai respons terhadap munculnya berbagai jenis penghasilan yang tidak secara eksplisit disebutkan dalam fikih klasik. Di Aceh, zakat profesi dikelola oleh Baitul Mal Aceh sebagai lembaga resmi pengelola zakat, infak, dan sedekah. Penelitian ini bertujuan menganalisis standar perhitungan zakat profesi yang diterapkan Baitul Mal Aceh, dasar hukum dan pertimbangan yang digunakan, serta kesesuaiannya dengan prinsip syariah dan regulasi yang berlaku. Metode penelitian yang digunakan adalah kualitatif deskriptif-analitis melalui studi dokumen dan literatur terkait. Hasil penelitian menunjukkan bahwa standar perhitungan zakat profesi di Baitul Mal Aceh disusun berdasarkan ketentuan syariat Islam, fatwa ulama, serta regulasi nasional dan daerah, khususnya Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh dan Qanun Aceh Nomor 10 Tahun 2018 tentang Baitul Mal. Penetapan nisab, kadar zakat, dan mekanisme penghitungan mengacu pada qiyas zakat emas dan perak sebesar 2,5% dari pendapatan yang mencapai nisab setara 94 gram emas murni. Dewan Pertimbangan Syariah Baitul Mal berperan penting dalam memberikan fatwa dan pengawasan syar'i terhadap kebijakan pengelolaan zakat profesi. Dengan demikian, standar perhitungan zakat profesi di Baitul Mal Aceh telah sejalan dengan prinsip syariah dan regulasi nasional, serta mencerminkan upaya profesionalisasi dan transparansi dalam pengelolaan zakat di Aceh.